2018
DOI: 10.3390/en11030494
|View full text |Cite
|
Sign up to set email alerts
|

Biological Pretreatment of Mexican Caribbean Macroalgae Consortiums Using Bm-2 Strain (Trametes hirsuta) and Its Enzymatic Broth to Improve Biomethane Potential

Abstract: The macroalgae consortium biomass in the Mexican Caribbean represents an emerging and promising biofuel feedstock. Its biological pretreatment and potential for energetic conversion to biomethane were investigated, since some macroalgae have hard cell walls that present an obstacle to efficient methane production when those substrates are used. It has been revealed by anaerobic digestion assays that pretreatment with a Bm-2 strain (Trametes hirsuta) isolated from decaying wood in Yucatan, Mexico was 104 L CH 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 28 publications
(45 reference statements)
4
36
4
Order By: Relevance
“…Biological pretreatment is another environmental friendly method which uses rot fungi to decompose some of the biomass components to make it easier to process in pyrolysis [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203] . Various types of rot fungi including brown, white and soft rot ones can be used.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…Biological pretreatment is another environmental friendly method which uses rot fungi to decompose some of the biomass components to make it easier to process in pyrolysis [186][187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203] . Various types of rot fungi including brown, white and soft rot ones can be used.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…Biological pretreatment consists of the use of biological microorganisms (such as fungi or bacteria) and/or enzymes (enzyme-assisted extraction) for the degradation of any component of the biomass (Thompson et al, 2019). These pretreatments are cost-effective, ecologically friendly and can be used aerobically or anaerobically (Tapia-Tussell et al, 2018). Regarding the enzymes, they are chosen depending on the main components of biomass, such as cellulose, hemicelluloses, glycoproteins, pectin or even lignin.…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…The most employed microorganisms for the production of enzymes are fungi, specially the white rot fungi (Trametes sp. ), which produces the enzymes manganese peroxidase, lignin peroxidase and laccase, that can efficiently degrade the lignin (Tapia-Tussell et al, 2018;Thompson et al, 2019). Other promising candidates for the production of enzymes are Trichoderma, Penicillium, Fusarium, Phanerochaete, Humicola and Schizophillum (Soliman et al, 2018).…”
Section: Biological Pretreatmentmentioning
confidence: 99%
“…The twenty-one published papers cover a variety of biomass or waste residuals that have been converted into different types of energy, biofuels or biochemicals including heat [1,11,16], methane [2,4,[7][8][9]17,[19][20][21], electricity [2,11,16], short chain fatty acids [2,19], ethanol [3,12,19], syngas [5,19], nutrient pellets [6], hydroxymethylfurfura [15], and hydrogen [2,10,14,18,19]. The key information including biomass or residuals, products, and technology for the production and type of research are summarized in Table 1.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…Tapia-Tussell et al [17] investigated the potential for energetic macroalgae conversion to biomethane using biological pretreatment. Their results revealed that an increase in methane yield of 20% was achieved by using fungus for pretreatment.…”
Section: Brief Overview Of the Contributions To This Special Issuementioning
confidence: 99%